Moderate Impact of Tax Understanding on The Effect of Theory Planned of Behavior on Taxpayer Compliance of Pamekasan MSMEs - Wahyu Maulana; Very Andrianingsih (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This research is motivated by the level of compliance of taxpayers who are not fully in accordance with reporting their taxes. Of course this is caused by several psychological factors and one of them, where these psychological factors include subjective norms, attitudes and behavioral control. The purpose of this study was to determine the impact of tax understanding moderation on the effect of the theory of planned behavior on taxpayer compliance. The object of this research is Pamekasan SMEs registered at the Pamekasan Tax Office. The results showed that there was a significant positive effect between the independent variables on taxpayer compliance but for the behavioral control variable the effect was not significant positive and for tax understanding showed insignificant results as a moderator between the relationship between subjective norms and attitudes towards taxpayer compliance but significant as a moderator between the control relationship behavior towards taxpayer compliance